Role of necroptosis and immune infiltration in essential thrombocytosis - Guangming Li; Ying Guo; Yuanyuan Zhang (Hereditas)
Abstract Background Necroptosis, a recently identified form of programmed cell death involved in the pathogenesis of a variety of tumor and non-tumor diseases. Nevertheless, the function of necroptosis in essential thrombocytosis (ET) remains unclear, which is a classic myeloproliferative tumor. Materials and methods The role of necroptosis in ET was determined via bioinformatics combined with qRT-PCR analysis of clinical samples. GSE57793 and GSE26049 datasets were recruited to identify necroptosis differentially expressed genes based on differential gene identification, necroptosis gene sets and data machine learning. Enrichment analysis (GSEA) was used to evaluate the gene enrichment signaling pathway of ET, immune infiltration analysis was used to explore the abundance of immune cell infiltration in ET, and the correlation between necroptosis differential genes and immune cell infiltration was studied. Results Five necroptosis genes were recognized to be remarkably enriched in the necroptosis pathway, including CHMP1B, FTH1, HSP90AB1, IL1A, and RBCK1. The imbalance of invasion of Th1/Th17 cells was identified in ET, and the differential necroptosis gene was positively correlated with the infiltration of multiple immune cells. There is significant necroptosis in ET, which is enriched in the necrotizing apoptotic pathway, and is associated with immune infiltration. Conclusions Necroptosis might drive the progression of ET via stimulating immune infiltration and immune responses. The findings bring new insights into the treatment mechanism and treatment strategy of ET in the future.